Contrast‐Enhanced Brain Ultrasound Perfusion Metrics in the EXTra‐Uterine Environment for Neonatal Development (EXTEND): Correlation With Hemodynamic Parameters. (29th January 2021) - Lawrence, Kendall M.; Coons, Barbara E.; Sridharan, Anush; Davey, Marcus G.; Flake, Alan W.; Didier, Ryne A.
Abstract : Objectives: Contrast‐enhanced ultrasound (CEUS) can provide quantitative perfusion metrics and may be useful to detect cerebral pathology in neonates and premature infants, particularly in extrauterine environments. The effect of hemodynamics on cerebral perfusion metrics is unknown, which limits the clinical application of this technology. We aimed to determine associations between systemic hemodynamics and concurrently measured brain perfusion parameters in an animal model of extrauterine support. Methods: Nine fetal lambs were transferred to an extrauterine support device. Lumason® ultrasound contrast (0.1–0.3 ml) was administered via the umbilical vein and 90‐second cine clips were obtained. Time‐intensity‐curves (TICs) were generated and time‐dependent and area‐under‐curve (AUC) parameters were derived. Associations between brain perfusion metrics and hemodynamics including heart rate (HR) and mean arterial pressure (MAP) were evaluated by multilevel linear mixed‐effects models. Results: Eighty‐six ultrasound examinations were performed and 72 examinations were quantifiable. Time‐dependent measurements were independent of all hemodynamic parameters (all p ≥.05). Oxygen delivery and mean blood flow were correlated with AUC measurements (all p ≤.01). Physiologic HR and MAP were not correlated with any measurements (all p ≥.05). Conclusion: Detected aberrations in time‐dependent CEUS measurements are not correlated with hemodynamic parameters and are thought to reflect the changes in cerebral blood flow, thus providing a promising tool for evaluation of brain perfusion. CEUS brain perfusion parameters are not correlated with physiologic HR and MAP, but AUC‐dependent measurements are correlated with oxygen delivery and blood flow, suggesting that CEUS offers additional value over standard monitoring. Overall, these findings enhance the applicability of this technology.